Interactive training course to develop information and communication competences in sport school coaches - Polyak , D.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test benefits of a new interactive training course, complementary to the advanced training system, to develop information communication competences and skills in the sport school coaches. Methods and structure of the study. Information and communication competences may be defined as the "professionally important integrative personality knowledgebase and skills to independently find, process, analyze and present necessary information; model and design the relevant objects and processes; and implement the relevant projects by both individual and group efforts". In the information and communication competence training course, the students were trained to actively communicate using the modern communication tools (Zoom, WhatsApp, Telegram, e-mail, etc.); develop joint products including elements of the training service plans and reports in the text processors; elements of the physical fitness and competitive success monitoring systems with reports and graphical presentations on a Google disk, etc. Results and conclusion. The new information and communication competence training course piloting project was finalized by the group Digital Coaching Office projects submitted by the trainees for discussions, evaluations and progress scores. Based on the scores and final IT/ communication knowledge and skill tests, we rated the information and communication competence of every trainee. A progress analysis found the information and communication competence growing on average by 2% and 5% in the knowledge and skills domains, respectively. The new interactive training course, complementary to the advanced training and retraining system, to develop information communication competences and skills in the sport school